Novel frequency selective structures based on a two-dimensional periodic array of vertical microstrip lines - Amir Khurrum Rashid (2011)
A novel frequency selective structure (FSS) consisting of a two-dimensional (2-D) periodic array of vertical microstrip lines has been proposed. Under plane wave incidence whose polarization is perpendicular to the strips, this array supports two quasi-TEM modes. Controlling the propagation constants and the coupling of these modes with air, it is possible to obtain a quasi-elliptic filtering response. Further, due the existence of quasi-TEM modes, it is easy to use the unit-cells of sub-wavelength size, which leads to stable performance under large variation of the angle of incidence. This FSS has been investigated using an efficient full-wave mode-matching method. The analysis comprises two parts. First, the propagation characteristics of the 2-D array are studied by solving a unit-cell of this structure, which is sandwiched between two periodic boundaries. In the second part, an air-to-array discontinuity is solved using Floquet modes in the air-region. Based on the full-wave analysis, a number of FSSs have been fabricated, which exhibit stable quasi-elliptic filtering response under a large variation of the angle of incidence. Results of the full-wave analysis are in excellent agreement with those obtained from measurements and CST Microwave Studio. Further, a wideband circuit analogue microwave absorber has also been proposed which is based on a similar structure, and exhibits more than 110% bandwidth.